2014
DOI: 10.1111/jcpt.12124
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk-factors of CHOP/R-CHOP-related cardiotoxicity in patients with aggressive non-Hodgkin's lymphoma

Abstract: Our study confirmed the weight of cardiac toxic effect of CHOP ± R regimen. Even if the use of dexrazoxane is highly debatable in curative situations, it may be an effective prevention of cardiotoxicity in aggressive NHL patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 38 publications
1
25
0
3
Order By: Relevance
“…U starszych pacjentów z uprzednio stwierdzonymi czynnikami ryzyka CV krótkoterminowe ryzyko wystąpienia HF również jest zwiększone. Na przykład, wśród pacjentów, którzy przebyli agresywnego chłoniaka nieziarniczego, 5-letnia zapadalność na jawną klinicznie HF wynosi 17% [8]. Zwiększa się również świadomość występowania dysfunkcji LV lub HF wywoły-wanej przez inhibitory kinaz tyrozynowych (TKI), zwłaszcza u pacjentów onkologicznych z uprzednio występującymi czynnikami ryzyka CV [9].…”
Section: Patofizjologia I Obraz Klinicznyunclassified
“…U starszych pacjentów z uprzednio stwierdzonymi czynnikami ryzyka CV krótkoterminowe ryzyko wystąpienia HF również jest zwiększone. Na przykład, wśród pacjentów, którzy przebyli agresywnego chłoniaka nieziarniczego, 5-letnia zapadalność na jawną klinicznie HF wynosi 17% [8]. Zwiększa się również świadomość występowania dysfunkcji LV lub HF wywoły-wanej przez inhibitory kinaz tyrozynowych (TKI), zwłaszcza u pacjentów onkologicznych z uprzednio występującymi czynnikami ryzyka CV [9].…”
Section: Patofizjologia I Obraz Klinicznyunclassified
“…Perhaps one of the best pieces of evidence that iron plays a pivotal role in the ROS-mediated toxicity of DOX comes from numerous studies showing that the iron chelator dexrazoxane (DEX) can effectively block anthracycline cardiotoxicity [138]. It has been repeatedly shown to mitigate anthracycline toxicity, and is approved for clinical use [150-152]. Marty et al have shown in a randomized phase III study of 164 breast cancer patients that in comparison to patients receiving an anthracycline alone, patients treated with both an anthracycline and DEX experienced significantly fewer and less severe episodes of congestive heart failure, without affecting the tumor response rate [116].…”
Section: Strategies To Improve Clinical Response And/or Reduce Clinicmentioning
confidence: 99%
“…There again, the interval between treatment and the onset of the stroke or myocardial infarction event is relatively short (2.5 [1.8 --3.4] and 3.7 [1.6 --5.1] respectively) but they were not associated with chemotherapy [4]. Furthermore, it is currently estimated that 5% of patients treated with CHOP will sustain myocardial damage sufficient to cause chronic heart failure [6] and evidence from Hodgkin lymphoma studies would also suggest a higher prevalence of subclinical injuries that can evolve into clinical lesions [7]. Box 1.…”
Section: Cardiotoxicity Anthracyclines and Nhlmentioning
confidence: 99%